Edukasi Perilaku Keuangan Keluarga yang Baik Saat Bulan Ramadhan pada TPA IT Baiti Jannati Surakarta - Amalia, Naili; Hamdani, Muhammad Luthfi (Universitas Ekuitas Indonesia, 2024)
The month of Ramadan is known to be the peak of economic liquidity where household spending increases rapidly. So it is necessary for every household to prepare themselves so as not to be trapped in detrimental financial behavior. Good financial behavior can be seen from the decision to use money when faced with needs that must be spent effectively, for saving, and for investment. Education on family financial behavior is carried out in the parent parenting class of TPA IT Baiti Jannati, Surakarta. The method of this service is education through problem identification, presentation of material, and discussion. Some of the parenting participants said that there was minimal financial preparation for Ramadan. Mental and psychological readiness in facing Ramadan is the main key to avoid pressure and stress due to increased spending. Therefore, a special plan is needed to face Ramadan by implementing strategies to increase income, managing personal finances, implementing coping strategies with planful problem solving, self control, utilising technology and financial technology. It is strongly recommended and recommended that before Ramadan, you must have prepared Ramadan finances by making Ramadan Savings. In addition, you must be wise in shopping, manage finances in such a way that all needs are fulfilled without any deficit or debt. The existence of this activity is expected that participants have better knowledge related to financial behaviour and can make wiser financial decisions during the month of Ramadan with the use of financial infrastructure. Keywords: Financial decisions, financial behavior, month of ramadan. Abstrak Bulan Ramadhan diketahui menjadi puncak likuiditas perekonomian dimana pengeluaran rumah tangga meningkat pesat. Sehingga perlu setiap rumah tangga perlu mempersiapkan diri agar tidak terjebak pada perilaku keuangan yang merugikan. Adapun perilaku keuangan yang baik bisa dilihat dari keputusan penggunaan uang di saat dihadapkan pada kebutuhan yang harus dikeluarkan secara efektif, untuk menabung, dan untuk investasi Edukasi perilaku keuangan keluarga dilakukan pada kelas parenting wali murid TPA IT Baiti Jannati, Surakarta. Metode dalam pengabdian ini berupa edukasi melalui identifikasi masalah, pemaparan materi, dan diskusi. Beberapa dari peserta parenting mengakatakan jika memang minim akan persiapan keuangan menghadapi Ramadhan. Kesiapan mental dan psikis dalam menghadapi Ramadhan kunci utama untuk menghindari adanya tekanan dan stress karena peningkatan pengeluaran. Maka dari itu perlu rencana khusus untuk menghadapi Ramadhan dengan menerapkan strategi peningkatan pendapatan, pengelolaan keuangan pribadi, penerapan strategi coping dengan planful problem solving, self control, pemanfaatam teknologi dan financial teknologi. Sangat disarankan dan dianjurkan sebelum Ramadhan harus sudah mempersiapkan keuangan Ramadhan dengan cara membuat Tabungan Ramadhan. Selain itu harus bijak dalam berbelanja, kelola keuangan sedemikian rupa hingga terpenuhinya semua kebutuhan tanpa adanya defisit atau hutang. Adanya kegiatan ini peserta diharapkan memiliki pengetahuan lebih baik terkait perilaku keuangan dan bisa mengambil keputusan keuangan yang lebih bijak selama bulan Ramadhan dengan pemanfaatan insfrastruktur financial. Kata Kunci: Keputusan keuangan, perilaku keuangan, bulan ramadhan.